2006
DOI: 10.1111/j.1399-6576.2006.01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac output – pulse contour analysis vs. pulmonary artery thermodilution

Abstract: Background: The aims of this study were to determine the agreement between pulmonary artery thermodilution (PA-TD), transpulmonary thermodilution (TP-TD) and the pulse contour method, and to test the ability of the pulse contour method to track changes in cardiac output. Methods: Cardiac output was determined twice before cardiac surgery with both PA-TD and TP-TD. The precision (two standard deviations of the difference between repeated measurements) and agreement of the two methods were calculated. Post-opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…PCA analysis from a peripheral arterial pressure signal is traditionally considered less accurate because curve damping and wave reflection can induce important errors. Nevertheless, data from the present study compare well to published data on accuracy with the PiCCO system and suggest that the PulseCo algorithm may be relatively insensitive to such artifacts [7,17,18]. We need to emphasize that our results were obtained in patients undergoing OPCAB surgery, a peculiar type of cardiac surgery for which extracorporeal circulation is not used.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…PCA analysis from a peripheral arterial pressure signal is traditionally considered less accurate because curve damping and wave reflection can induce important errors. Nevertheless, data from the present study compare well to published data on accuracy with the PiCCO system and suggest that the PulseCo algorithm may be relatively insensitive to such artifacts [7,17,18]. We need to emphasize that our results were obtained in patients undergoing OPCAB surgery, a peculiar type of cardiac surgery for which extracorporeal circulation is not used.…”
Section: Discussionsupporting
confidence: 84%
“…The clinical value of a CO monitoring system also depends on its ability to monitor trends and to correctly quantify changes in CO. Only few studies have addressed this issue [18,[22][23][24]. We administered low-dose dobutamine to a small number of patients after complete revascularization.…”
Section: Before Dobutamine After Dobutaminementioning
confidence: 99%
“…It has been shown that a threemeasurement set gives good reproducibility for cardiac output in different patients using the double-indicator dilution technique [4,16]. However, there is no unambiguous agreement on the minimum injection number in the measurement of cardiac output by pulmonary artery catheter [3,17] despite this technique being held as a 'clinical gold standard' in several ICUs.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have examined the correlation between APWA-derived and PAC-derived CO measurements in cardiac surgical patients, both intra-operatively [32,41,52,53] and postoperatively [54][55][56][57][58]. In a series of 24 postoperative cardiac surgical patients, Goedje et al…”
Section: Value Of Arterial Pulse Wave Analysis In Assessing Cardiac Omentioning
confidence: 98%